2023
DOI: 10.1038/s41598-023-33369-8
|View full text |Cite
|
Sign up to set email alerts
|

STEP-COVID: a pilot study of a prenatal intervention for pregnant women during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has been associated with a global increase in psychological distress in pregnant women. This study evaluated the effects of STEP-COVID, a six-session mentalization-based prenatal group program offered online during the COVID-19 pandemic. The 100 participants were allocated to STEP-COVID or to the natural trajectory of prenatal care. Pre- and post-intervention assessments included measures of psychological distress, post-traumatic symptoms and positive affectivity. Perception of change dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…When the participant was no longer in a relationship with the partner, the items were answered in relation to the other parent. The five items evaluate satisfaction, communication, ability to confide in the partner, interest toward the partner's feelings and emotional support offered to the partner (see Berthelot et al, 2023). Both the total score and scores at each item were used in the present study.…”
Section: Changes In Couple Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…When the participant was no longer in a relationship with the partner, the items were answered in relation to the other parent. The five items evaluate satisfaction, communication, ability to confide in the partner, interest toward the partner's feelings and emotional support offered to the partner (see Berthelot et al, 2023). Both the total score and scores at each item were used in the present study.…”
Section: Changes In Couple Functioningmentioning
confidence: 99%
“…The program differed from the original program in that the specific content on childhood adversity was shortened and reworked to be more inclusive, and some activities were adapted to address specific issues related to the pandemic. A preliminary evaluation of STEP-COVID showed that women who participated in the intervention, and not women receiving treatment-as-usual (TAU), showed a significant decrease in psychological distress and a significant increase in positive affectivity over the course of pregnancy (Berthelot et al, 2023). Participants in STEP-COVID also reported significant changes during the program on resilience-promoting factors .…”
Section: Statement Of Relevancementioning
confidence: 99%